2015
DOI: 10.1080/02640414.2015.1026378
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breast support and breast pain on upper-extremity kinematics during running: implications for females with large breasts

Abstract: The relationship between inappropriate breast support and upper-extremity kinematics for female runners is unclear. The purpose of this study was to investigate the effect of breast support and breast pain on upper-extremity kinematics during running. Eleven female recreational runners with larger breasts (UK D and E cup) completed a 7 min 20 s treadmill run (2.58 m · s(-1)) in a high and low breast support condition. Multi-planar breast and upper-extremity kinematic data were captured in each breast support c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
0
21
1
Order By: Relevance
“…While not the primary focus of this investigation, perception of each smart bra was collected from participants. A number of factors have been identified in the literature that affect the perception of sports bra comfort during exercise including breast asymmetry 38 , quality of support 39 , and design aspects accounting for cushioning 40 , strap Table 3. Percent of erroneous heart rate values produced during each condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not the primary focus of this investigation, perception of each smart bra was collected from participants. A number of factors have been identified in the literature that affect the perception of sports bra comfort during exercise including breast asymmetry 38 , quality of support 39 , and design aspects accounting for cushioning 40 , strap Table 3. Percent of erroneous heart rate values produced during each condition.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ placement 41 , and fabric and thermal properties 42,43 . Women who ran on a treadmill while wearing a high support sports bra rated their experience as more comfortable with less pain than while wearing a low support bra 39 . The bra strap contributes to the most overall discomfort during exercise 41 , and a cross-strap design with cushioning may help to reduce the distress 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Schoolgirls were categorised as having smaller breasts (≤ C cup; 78%) or larger breasts (≥ D cup; 22%) (Dundas et al, 2007;Scurr et al, 2011;Brown et al, 2014a,b;White et al, 2015).…”
Section: Data Handling and Statistical Analysismentioning
confidence: 99%
“…While most of the breast movement occurs vertically, some studies found that the different sizes and shapes of breasts do not follow the same distribution of displacement. White et al (2015) suggested that the reduction of breast motion in the anteroposterior direction should be considered by the sports bra designers, in order to help reduce breast pain for female runners with larger breasts.…”
Section: )mentioning
confidence: 99%
“…At the breast support level, other wool patch designs should be investigated, as suggested by the extensive breast support literature. White et al (2015) suggested that the reduction of breast motion in the anteroposterior direction should be considered by the sports bra designers, in order to help reduce breast pain for female runners with larger breasts. Therefore, different placement and considerations for responsiveness of the materials could be explored.…”
Section: Future Researchmentioning
confidence: 99%